Clinical management and mortality among COVID-19 cases in sub-Saharan Africa: A retrospective study from Burkina Faso and simulated case analysis. (December 2020) - Skrip, Laura; Derra, Karim; Kaboré, Mikaila; Noori, Navideh; Gansané, Adama; Valéa, Innocent; Tinto, Halidou; Brice, Bicaba W.; Gordon, Mollie Van; Hagedorn, Brittany; Hien, Hervé; Althouse, Benjamin M.; et al.
Highlights: Countries within the sub-Saharan Africa (SSA) region may experience high COVID-19 case fatality rates. Over the first months of the epidemic in SSA, deceased cases have tended to mainly be male, aged >50 years and have underlying comorbidities. Delayed or no care-seeking was prevalent among deceased COVID-19 cases in Burkina Faso. Analysis on a synthetic case population suggested that treatment with oxygen therapy or convalescent plasma reduced the adjusted odds of COVID-19 mortality. Low-cost, scalable and sustainable strategies for COVID-19 case management in the SSA context warrant attention and investment to reduce disparity in case fatality. Abstract: Background: Absolute numbers of COVID-19 cases and deaths reported to date in the sub-Saharan Africa (SSA) region have been significantly lower than those across the Americas, Asia and Europe. As a result, there has been limited information about the demographic and clinical characteristics of deceased cases in the region, as well as the impacts of different case management strategies. Methods: Data from deceased cases reported across SSA through 10 May 2020 and from hospitalized cases in Burkina Faso through 15 April 2020 were analyzed. Demographic, epidemiological and clinical information on deceased cases in SSA was derived through a line-list of publicly available information and, for cases in Burkina Faso, from aggregate records at the Centre Hospitalier Universitaire de Tengandogo in Ouagadougou. A synthetic case population was probabilistically derived using distributions of age, sex and underlying conditions from populations of West African countries to assess individual risk factors and treatment effect sizes. Logistic regression analysis was conducted to evaluate the adjusted odds of survival for patients receiving oxygen therapy or convalescent plasma, based on therapeutic effectiveness observed for other respiratory illnesses. Results: Across SSA, deceased cases for which demographic data were available were predominantly male (63/103, 61.2%) and aged >50 years (59/75, 78.7%). In Burkina Faso, specifically, the majority of deceased cases either did not seek care at all or were hospitalized for a single day (59.4%, 19/32). Hypertension and diabetes were often reported as underlying conditions. After adjustment for sex, age and underlying conditions in the synthetic case population, the odds of mortality for cases not receiving oxygen therapy were significantly higher than for those receiving oxygen, such as due to disruptions to standard care (OR 2.07; 95% CI 1.56–2.75). Cases receiving convalescent plasma had 50% reduced odds of mortality than those who did not (95% CI 0.24–0.93). Conclusions: Investment in sustainable production and maintenance of supplies for oxygen therapy, along with messaging around early and appropriate use for healthcare providers, caregivers and patients could reduce COVID-19 deaths in SSA. Further investigation into convalescent plasma is warranted until data on its effectiveness specifically in treating COVID-19 becomes available. The success of supportive or curative clinical interventions will depend on earlier treatment seeking, such that community engagement and risk communication will be critical components of the response.